2021
DOI: 10.3390/fluids6120429
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic Particle Image Velocimetry and Dynamic Mode Decomposition (DMD) in a Rectangular Impinging Jet: Vortex Dynamics and Acoustic Generation

Abstract: Impinging jets are encountered in ventilation systems and many other industrial applications. Their flows are three-dimensional, time-dependent, and turbulent. These jets can generate a high level of noise and often present a source of discomfort in closed areas. In order to reduce and control such mechanisms, one should investigate the flow dynamics that generate the acoustic field. The purpose of this study is to investigate the flow dynamics and, more specifically, the coherent structures involved in the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Assoum et al [19][20][21][22][23][24] studied the configuration of a rectangular jet impinging on a slotted plate (slot tones) using stereoscopic and tomographic particle image velocimetry techniques. The authors showed that the sound emission was obtained by energy transfer from the aerodynamic to the acoustic modes and that the aerodynamic modes directly affected the self-sustained frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Assoum et al [19][20][21][22][23][24] studied the configuration of a rectangular jet impinging on a slotted plate (slot tones) using stereoscopic and tomographic particle image velocimetry techniques. The authors showed that the sound emission was obtained by energy transfer from the aerodynamic to the acoustic modes and that the aerodynamic modes directly affected the self-sustained frequencies.…”
Section: Introductionmentioning
confidence: 99%